Direct identification of clinically relevant neoepitopes presented on native human melanoma tissue by mass spectrometry - Michal Bassani-Sternberg (Nature Portfolio, 2016)
Neoantigens determine anti-cancer immunoreactivity and are important functional targets for immunotherapy. Here, the authors use deep mass spectrometry to characterize neoepitopes from human melanoma tissue and show the presence of tumour-reactive T cells with specificity for selected neoantigens.